Consider the following equations:
x 2 − y 2 = 2 5
x 2 + x + x y + y + y 2 = 4 9 4
x 3 − y 3 = 4 6 9
Find x+y
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
i cant get it, please explain.
Log in to reply
There is nothing here to not understand. He simply added the 1st and 3rd equations and split the parts using identities x 2 − y 2 = ( x + y ) ( x − y ) and x 3 − y 3 = ( x − y ) ( x 2 + y 2 + x y ) .
Then, he took ( x − y ) as a common factor from both parts and substituted the value of ( x 2 + x y + y 2 + x + y ) from the 2nd equation to get ( x − y ) = 1
He substituted the value of ( x − y ) in the identity x 2 − y 2 = ( x + y ) ( x − y ) and used the given value of ( x 2 − y 2 ) to finally find out ( x + y ) = 2 5
Which part?
13^2 - 12^2 = 169-144 = 25 so...12+13
Rewrite: x 2 − y 2 = 2 5 x 2 + x + x y + y + y 2 = 4 9 4 x 3 − y 3 = 4 6 9 ⇒ ( x + y ) ( x − y ) = 2 5 ⇒ ( x + y ) + ( x 2 + x y + y 2 ) = 4 9 4 ⇒ ( x − y ) ( x 2 + x y + y 2 ) = 4 6 9 Let a = x + y , b = x − y , and c = x 2 + x y + y 2 , then a b = 2 5 a + c = 4 9 4 b c = 4 6 9 ( 1 ) ( 2 ) ( 3 ) from ( 1 ) and ( 3 ) , we obtain a b b c a c c = 2 5 4 6 9 = 2 5 4 6 9 = 2 5 4 6 9 a Pluging in the last part to ( 2 ) , yield a + 2 5 4 6 9 a 2 5 4 9 4 a a = 4 9 4 = 4 9 4 = 2 5 . Thus, a = x + y = 2 5 .
x^2 + y^2 + xy + (x + y) = 494---------(iii) Now, x^2 + y^2 + xy = (x^3 - y^3) / (x - y) = 469 / (x - y)---(i) Now , (x - y)(x + y) = 25 , (x - y) = 25 / (x + y)---(ii) Substituting (ii) in (i) , 469 / ( 25 / (x + y) ) = 469(x+y)/25 Let , (x + y) = z Putting all values in (iii) 469z/25 + z = 494 469z + 25z = 12350 494z = 12350 z = 12350 / 494 z = 25 But , z = (x + y) Ans: (x + y) = 25
its damn easy... by common sense, we know that 13^2 - 12^2 = 25. (remember Pythagoras triplets) so x=13 and y=13. so x+y= 25.
x^2+x+xy+y+y^2=494, (x-y)(x^2+x+xy+y+y^2)=494(x-y), (x-y)(x^2+xy+y^2)+(x+y)(x-y)=494(x-y), (x^3-y^3)+x^2-y^2=494(x-y), 469+25=494(x-y), 494=494(x-y), x-y=1. Again, x^2-y^2=25, (x+y)(x-y)=25, (x+y)*1=25, x+y=25.
Problem Loading...
Note Loading...
Set Loading...
x 2 − y 2 + x 3 − y 3 = 4 9 4
( x − y ) ( x + y ) + ( x − y ) ( x 2 + x y + y 2 ) = 4 9 4
( x − y ) ( x 2 + x y + y 2 + x + y ) = 4 9 4
( x − y ) × 4 9 4 = 4 9 4
( x − y ) = 1
Now, x 2 − y 2 = 2 5
( x − y ) ( x + y ) = 2 5
( x + y ) = 2 5